An interconnection between morphological and functional development of highly trained swimmers and a result of overcoming different length distances by means of the butterfly stroke - Пилипко, Ольга; Пилипко, Аліна (Slobozhanskyi Herald of Science and Sport, 2017)
Olga Pilipko & Alina Pilipko Purpose: to investigate the influence of indicators of morpho-functional development of highly trained swimmers on the result of overcoming different length distances by means of the butterfly stroke. Material & Methods: analysis of scientific and methodical literature, timing, measurement of morphological and functional indicators using individual techniques, methods of mathematical statistics. Contingent surveyed accounted for athletes who specialize in the distances of 50, 100 and 200 meters by means of the butterfly stroke and had a level of sports qualification: master of sports, international class master of sports. Results: the authors determined the relationship between the degree of correlation of morphological and functional performance highly trained swimmers and sports results at distances of 50, 100 and 200 meters by means butterfly stroke; investigated the significance of morpho-functional indicators, depending on the length of the competitive distance. Conclusion: significance of the indicators of anthropometric development and the functional state of athletes who specialize in swimming by means butterfly stroke differs depending on the length of the competitive distance. The definition of distance specialization of athletes by means butterfly stroke should be carried out taking into account the indicators of morpho-functional development, which most significantly affect the result of overcoming the distances of 50, 100 and 200 meters.